THE LINK BETWEEN CHOLECALCIFEROL INTAKE AND MANIFESTATIONS OF DEPRESSION AND MENSTRUAL ANOMALIES IN PREMENSTRUAL SYNDROME - NAEEM , A; SHAIKH , K; BATOOL , S; ANESS, A; MUMTAZ , S; SIDDIQUI , K (Biological and Clinical Sciences Research Journal, 2023)
Diminished vitamin D levels have been linked to manifestations of premenstrual discomfort and mood disturbances. Our study delved into the connection between reduced cholecalciferol concentrations and depressive tendencies alongside diverse menstrual inconsistencies observed in individuals with PMS. A cross-sectional study was conducted involving 250 female participants sourced from the Gynecology Outpatient Department at Liaquat University of Medical & Health Sciences (LUMHS), Jamshoro Hyderabad, Pakistan. This study encompassed women aged 15 to 45, especially those in good health but with a documented history of depression and PMS. The Beck Depression Inventory was employed to clinically assess the incidence of depression, while the premenstrual syndrome scale was utilized to gauge PMS. The Chi-square test was applied for statistical analysis to juxtapose two quantitative parameters: vitamin D levels and Beck’s scores, dysmenorrhea, menstrual flow, and age at menarche. Our analysis showed that 37.2% of the participants grappled with heavy menstrual flow, whereas 45.6% suffered from dysmenorrhea. Alarmingly, vitamin D was deficient in 61.2%, while an additional 34% displayed suboptimal levels. Regarding mental health indicators, 35.2% exhibited signs of mild depressive episodes during their premenstrual cycle, with a further 36.4% experiencing more acute depressive states. Among the vitamin D-deficient group, 18.8% were borderline for clinical depression, with 28.8% categorized under the severe depression bracket. Our statistical findings highlighted a pronounced linkage between Beck’s depression indices and vitamin D concentrations, yielding a P-value of 0.001. In dysmenorrhea, 39.6% of the afflicted females had compromised vitamin D levels. Additionally, vitamin D deficiency was present in 36.8% of participants reporting intense menstrual flow. Notably, 9.6% of females who reached menarche at 12 exhibited reduced vitamin D levels, compared to a mere 0.8% with early menarche and satisfactory vitamin D metrics. There appears to be an inverse relationship between vitamin D concentrations and depressive symptoms, suggesting that optimal vitamin D levels could potentially ameliorate depressive manifestations.